Testosterone alters iron metabolism and stimulates red blood cell production independently of dihydrotestosterone - Beggs, Luke A. (American Physiological Society, 2014)
Testosterone (T) stimulates erythropoiesis and regulates iron homeostasis. However, it remains unknown whether the (type II) 5α-reduction of T to dihydrotestosterone (DHT) mediates these androgenic effects, as it does in some other tissues. Our purpose was to determine whether inhibition of type II 5α-reductase (via finasteride) alters red blood cell (RBC) production and serum markers of iron homeostasis subsequent to testosterone-enanthate (TE) administration in older hypogonadal men. Sixty men aged ≥60 yr with serum T <300 ng/dl or bioavailable T <70 ng/dl received treatment with TE (125 mg/wk) vs. vehicle paired with finasteride (5 mg/day) vs. placebo using a 2 × 2 factorial design. Over the course of 12 mo, TE increased RBC count 9%, hematocrit 4%, and hemoglobin 8% while suppressing serum hepcidin 57% (P < 0.001 for all measurements). Most of the aforementioned changes occurred in the first 3 mo of treatment, and finasteride coadministration did not significantly alter any of these effects. TE also reduced serum ferritin 32% (P = 0.002) within 3 mo of treatment initiation without altering iron, transferrin, or transferrin saturation. We conclude that TE stimulates erythropoiesis and alters iron homeostasis independently of the type II 5α-reductase enzyme. These results demonstrate that elevated DHT is not required for androgen-mediated erythropoiesis or for alterations in iron homeostasis that would appear to support iron incorporation into RBCs.